2018
DOI: 10.1155/2018/2680121
|View full text |Cite
|
Sign up to set email alerts
|

Biological Resistance and Application Properties of Particleboards Containing Nano‐Zinc Oxide

Abstract: Special particleboards (PBs) proposed for kitchens, bathrooms, hospitals, and some other specific products for interiors should have a sufficient resistance against bacteria, molds, and decaying fungi. is work deals about effects of zinc oxide nanoparticles (nano-ZnO) added into melamine-urea-formaldehyde (MUF) glue in the amounts of 0, 2, 6, 12, or 24% wt. on selected biological, moisture, and strength properties of laboratory-produced one-layer PBs. e nano-ZnO-treated PBs had a higher biological resistance: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Nanoparticles of zinc oxide (ZnO) exhibit good antimicrobial activity. These nanoparticles are added into melamine-urea formaldehyde (MUF) glue before being used for particleboard production [ 115 ]. The findings show that there were increments in bioresistance of the particleboards against the Gram-positive bacterium Staphylococcus aureus , the Gram-negative bacterium Escherichia coli , the molds Aspergillus niger and Penicillium brevicompactum as well as the brown-rot fungus Coniophora puteana .…”
Section: Applicationsmentioning
confidence: 99%
“…Nanoparticles of zinc oxide (ZnO) exhibit good antimicrobial activity. These nanoparticles are added into melamine-urea formaldehyde (MUF) glue before being used for particleboard production [ 115 ]. The findings show that there were increments in bioresistance of the particleboards against the Gram-positive bacterium Staphylococcus aureus , the Gram-negative bacterium Escherichia coli , the molds Aspergillus niger and Penicillium brevicompactum as well as the brown-rot fungus Coniophora puteana .…”
Section: Applicationsmentioning
confidence: 99%
“…Recently, nano-based compounds (zinc and copper) have been applied wood surfaces in order to investigate resistance against termites and mold [27][28][29][30]. It has been shown that zinc-based compounds appeared to be more effective in terms of termite mortality and decay resistance against fungus, i.e., white-rot ( Figures 3 and 4).…”
Section: Increased Durabilitymentioning
confidence: 99%
“…Several studies related to wood color changes under high temperatures have been performed. With increased temperature and length of treatment, wood becomes darker [1,14,[24][25][26][27][28][29]. Color changes in thermally-treated wood are linked to the degradation of hemicelluloses and cellulose depolymerization [12], color changes in sap and extractives [30], loss of bending strength [1], and wood species [31].…”
Section: Introductionmentioning
confidence: 99%